Local Chlorhexidine Delivery for Periodontal Infection Therapy: A Short Review - Najmudin, Muhammad Guruh; Pangesty, Azizah Intan; Riastuti, Rini; Sunarso, Sunarso; Abdullah, Abdul Halim (UI Scholars Hub, 2023)
Oral diseases affected more than half of the world’s population. Periodontitis is the second biggest threat to oral health after dental caries. Periodontitis is an inflammation inside periodontal pockets caused by pathogenic microbial colonies which lead to destruction of bone tissue and soft tissue. Chlorhexidine gluconate is an antimicrobial agent that effective to destroy pathogenic microbial and cure periodontitis. Chlorhexidine gluconate is given locally using a carrier material to the infected area. There are several materials that can be used to deliver Chlorhexidine gluconate to the infected periodontal tissue such as gel, liquid (mouthwash), and chip. This short review aims to describe the current methods to deliver Chlorhexidine gluconate to the infected periodontal tissue, including the advantages, disadvantages, and the future trend of the carrier materials used for periodontitis treatment. Future research about materials that can help to optimize tissue restorative after cure periodontitis would be beneficial.